1999
DOI: 10.1093/jat/23.4.230
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cleanup and Determination of Dialkyl Phosphates in the Urine of Children Exposed to Organophosphorus Insecticides

Abstract: Analysis of dialkylphosphate urinary metabolites of organophosphorus insecticides has been used to estimate dose in nonoccupationally exposed populations, including children. Analytical methods must continue to be improved in order to accurately and reproducibly measure less than 10 ng/mL of these metabolites. Dialkyl phosphates are commonly determined as their pentafluorobenzyl bromide derivatives via gas chromatography (GC) with flame photometric detection. Presented here is an improved method for precleanup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 5 publications
2
66
0
1
Order By: Relevance
“…For example, a gummy syrup is produced after azeotropic distillation. Moate et al (1999) speculated that the alkylation of OP metabolites could be hindered by encapsulation of DAP metabolites in this gummy syrup. They found that a mixture of acetonitrile and dimethylformamide could dissolve the gummy residue and yield a better derivatization of DMP and DEP.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, a gummy syrup is produced after azeotropic distillation. Moate et al (1999) speculated that the alkylation of OP metabolites could be hindered by encapsulation of DAP metabolites in this gummy syrup. They found that a mixture of acetonitrile and dimethylformamide could dissolve the gummy residue and yield a better derivatization of DMP and DEP.…”
Section: Resultsmentioning
confidence: 99%
“…Because the alkylation of DAP metabolites is a thermosensitive reaction and the sulfur-containing DAPs degrade at high temperatures (Fenske and Leffingwell, 1989;Moate et al, 1999;Oglobline et al, 2001 a, b), optimization of the reaction temperature and time is critical. Typically, the sulfur-containing molecules (DMTP, DMDTP, DETP, and DEDTP) react at room temperature while DMP and DEP often require high temperatures to react.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations